Environmental and Social Management System Implementation Handbook : Crop Production - International Finance Corporation (Washington, DC, 2014)
This Handbook is intended to be a practical guide to help companies in the crop production industry develop and implement an environmental and social management system, which should help to improve overall operations. If a company has existing management systems for quality or health and safety, this Handbook will help to expand them to include environmental and social performance. Sections I and II provide background on environmental and social management systems (ESMS) in the crop production industry. Section III provides step-by-step instructions on how to develop and implement an ESMS. The ESMS Toolkit and Case Studies give tools to help develop and implement the systems described in the Handbook, and presents two case studies on companies in the crop production industry that implemented ESMS. For more publications on IFC Sustainability please visit www.ifc.org/sustainabilitypublications.